The housing community in Polish law: methods of management of communal areas - Sikorska-Lewandowska, Aleksandra (Studia Iuridica Toruniensia, 2017)
A housing community belongs to organisational units which are not legal persons but have legal capacity. The fundamental purpose of housing community activities is the management of common property. A specific feature of the Polish regulation is the distinction between “large” and “small” housing communities, on the basis of the criterion of the number of premises comprising the real property. To establish the rules of management of communal areas in Polish residential communities it is necessary in each case to determine whether an agreement changing the rules of management of communal areas has been entered into, and if not, to determine whether the housing community in question is “large” or “small”.